2022
DOI: 10.3390/molecules27123847
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of Six Pomegranate (Punica granatum L.) Varieties of Global Commercial Interest in Morocco: Pomological, Organoleptic, Chemical and Biochemical Studies

Abstract: Pomegranate variety properties are important not only to demonstrate their diversity but also to satisfy the current market need for high-quality fruits. This study aims to characterize pomological and physico-chemical features as well as the antioxidant capacity of Moroccan local cultivars (Djeibi, Mersi, Sefri 1 and Sefri 2) compared to the imported ones (Mollar de Elche and Hicaz). The pomological characteristics of varieties were relatively diverse. The juice varieties (PJ) displayed a marketed variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 63 publications
2
9
0
Order By: Relevance
“…As shown in Table 2, The pH value obtained for KH1 and HM1 is higher than some reported for Spanish, South African, Omani, Moroccan, Tunisian, Indian, Turkian, Iranian, Egyptian, Pakistani, Georgian pomegranate cultivars (Tehranifar et al, 2010;Ozlekci et al, 2011;Gadže et al, 2012;Caliskan & Bayazit, 2013;Ismail et al, 2014;Zaouay et al, 2014;Fernandes et al, 2017;Hota & Dahiya, 2017;Boussaa et al, 2018;Hmid et al, 2018;Usman et al, 2018;Díaz-Perez et al, 2019;Sassi et al, 2020;Meena et al, 2021;El Moujahed et al, 2022), while the pH value obtained for SL1 is closer to the values recorded on some Moroccan varieties such as "Jaune Marrakech" (Legua et al, 2011;Martínez et al, 2012), on Algerian cultivar "Doux de Koléa" (Meziane et al, 2016), on some Indian varieties such as Ganesh and Bhagwa (Hota & Dahiya, 2017) and on some pomegranate cultivars grown in Georgia (Díaz-Perez et al, 2019). Alcaraz-Mármol et al (2017) registered a higher pH than the reported values in the range of 6.02 to 6.78 for cultivars grown in Spain such as Mollar de Elche, Mollar de Orihuela and Valenciana de Albatera.…”
Section: Ph Titratable Acidity and Total Soluble Solidsmentioning
confidence: 61%
“…As shown in Table 2, The pH value obtained for KH1 and HM1 is higher than some reported for Spanish, South African, Omani, Moroccan, Tunisian, Indian, Turkian, Iranian, Egyptian, Pakistani, Georgian pomegranate cultivars (Tehranifar et al, 2010;Ozlekci et al, 2011;Gadže et al, 2012;Caliskan & Bayazit, 2013;Ismail et al, 2014;Zaouay et al, 2014;Fernandes et al, 2017;Hota & Dahiya, 2017;Boussaa et al, 2018;Hmid et al, 2018;Usman et al, 2018;Díaz-Perez et al, 2019;Sassi et al, 2020;Meena et al, 2021;El Moujahed et al, 2022), while the pH value obtained for SL1 is closer to the values recorded on some Moroccan varieties such as "Jaune Marrakech" (Legua et al, 2011;Martínez et al, 2012), on Algerian cultivar "Doux de Koléa" (Meziane et al, 2016), on some Indian varieties such as Ganesh and Bhagwa (Hota & Dahiya, 2017) and on some pomegranate cultivars grown in Georgia (Díaz-Perez et al, 2019). Alcaraz-Mármol et al (2017) registered a higher pH than the reported values in the range of 6.02 to 6.78 for cultivars grown in Spain such as Mollar de Elche, Mollar de Orihuela and Valenciana de Albatera.…”
Section: Ph Titratable Acidity and Total Soluble Solidsmentioning
confidence: 61%
“…The obtained extracts illustrated in Figure were previously characterized for their phenolic compositions and molecular size distributions (Figures S3 and S4 in Supporting Information). The results showed that the molecular weight distributions of their phenolic compounds were based on high molecular weight condensed tannins formed by the polymerization of the catechin monomer …”
Section: Resultsmentioning
confidence: 99%
“…Cross-linker extracts were carried out using the method reported in a previous work . Pomegranate rinds (PRs) were extracted using an aqueous-based solid–liquid method with heated ultrapure water at 20 °C, protected from light.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional approaches for pomegranate characterization include molecular [4], morphological [5] and biochemical analyses [6,7]; particular attention has been paid to qualitative characteristics of the main edible part of the fruit (the fleshy, membranous and pulpy part of the seed from which the juice is obtained), whereas fewer studies have been conducted on the hard part of the seeds, often erroneously called the "woody portion" or "seed" [8]. In this regard, it is worth noting that the botanical terms used to define the parts of the pomegranate fruit and seed are often used improperly in various scientific articles.…”
Section: Introductionmentioning
confidence: 99%